Direct current-enhanced densification kinetics during spark plasma sintering of tungsten powder. (15th January 2018) - Deng, Shenghua; Li, Ruidi; Yuan, Tiechui; Xie, Siyao; Zhang, Mei; Zhou, Kechao; Cao, Peng
Abstract: Rapid densification associated with spark plasma sintering has been well documented; however theoretical understanding is still very limited. In this work we proposed a densification creep model to explicitly elucidate the effect of current density on densification kinetics, by taking electromigration into account. This new model was then validated experimentally. It is found that an increased current density decreases densification activation energy (energy barrier), thus accelerating powder densification. In essence, the rapid densification is caused by direct current that accelerates mass transport and increases dislocation mobility. Graphical abstract: Image 1